Development and field testing of a consumer shared decision-making training program for adults with low literacy. Issue 10 (October 2015) - Muscat, Danielle M.; Morony, Suzanne; Shepherd, Heather L.; Smith, Sian K.; Dhillon, Haryana M.; Trevena, Lyndal; Hayen, Andrew; Luxford, Karen; Nutbeam, Don; McCaffery, Kirsten
Highlights We developed a comprehensive consumer SDM training program for adults with low literacy for delivery in education settings. The program aims to improve SDM knowledge, skills and self-efficacy. Consumer input was fundamental in our iterative development process.